Gain scheduled integral linear quadratic control for quadcopter - Shah, J; Okasha, M; Faris, W (International Journal of Engineering and Technology, 2018)
The findings of this paper are focused on the dynamics and control of a quadcopter using a modified version of a Linear Quadratic Regulator (LQR) control approach. The classical LQR control approach is extended to include an integral term to improve the quad copter tracking performance. The mathematical model is derived using the Newton-Euler method for the nonlinear six DOF model that includes the aerodynamics and detailed gyroscopic moments as a part of the system identification process. The linearized model is obtained and it is characterized by the heading angle (yaw angle) of the quadcopter. The adopted control approach is utilizing the LQR method to track several trajectories i.e. helical and lissajous curve with significant variation in the yaw angle. The integral term is introduced to the controller in order to minimize the steady state errors observed. The controller is modified to overcome difficulties related to the continuous changes in the operation points and to eliminate the chattering that was observed in the control technique. Numerical non-linear simulations are performed using MATLAB & Simulink to illustrate to accuracy and effectiveness of the proposed controller.Â Â Â